The impact of social media on people with disabilities as a tool for effective communication for the implementation policy of people in the team - Sedláková, Lucie; Mikulášková, Běla; Spáčilová, Veronika (Studia Sportiva, 2023)
Social medias is all around us, talking to us every step of the way, pulling us into the center of the action. We see the power of social media every day on popular websites. They control the masses of people, change attitudes to life, globalize and internationalize the entire planet. What is the place of a person with disabilities in this huge global group? Is it possible to use social media to connect people with disabilities to the world and bring them closer to other groups of people in society? Can a company reach and effectively integrate people with disabilities through social networks? The questions this research asks. Eurostat results from 2021 show that the Czech Republic is among the above-average countries with more than 62% of people aged 16-74 who have social networks. (EUROSTAT, 2021). The company can thus use this communication space effectively. The primary data was collected based on research conducted through in-depth interviews that addressed 12 respondents from 4 corporations, 2 focused on the provision of security services, and 2 private healthcare facilities. In-depth interviews were semi-structured and evaluated using descriptive statistics. Secondary data were used for a literature review on disability processing and social networks, see. List of sources. J The data has been processed in accordance with the ESOMAR Code of Conduct 2016. The survey will be part of further research after the application of the findings to verify the implementation policy. The survey was descriptive and conceptual with demoscopic elements. The research question was as follows: Is social media an appropriate tool for communicating with a new or existing team member with a disability? Based on this research question, a null hypothesis was established, people with disabilities prefer to communicate through social media because they are closer to them than through other communication media. Alternatively, people with disabilities do not prefer to communicate through social media because they are more familiar with other means of communication. The results were complemented by a questionnaire survey with 303 people with disabilities integrated into work and leisure time teams, eg. A team in the service industry working as security officers, a leisure group of readers of the working team of a medical facility, etc. The SPSS program was used for processing, where ANOVA and Kruskal-Wallis tests were performed. The results of the survey show a strong influence on social media on all team members with health impairments and are an effective implementation tool for communication.